Canopy management through crop forcing impacts the metabolism of phenolic compounds in grapevine canes - Teixeira, António; L. Cabral, Inês; Noronha, Henrique; Ferrier, Manon; Gémin, Marin-Pierre; Valente, Joana; Alves, Fernando; M. P. Carvalho, Susana; Queiroz, Jorge; Lanoue, Arnaud; Gerós, Hernâni (OENO one, 2025)
Despite extensive research on phenolic metabolism in grapevines, the effects of canopy management practices on the phenolic composition of woody canopy tissues remain insufficiently understood. This study investigates the impact of severe canopy management through crop forcing (CF) on the metabolic profile of grapevine canes cv. ‘Touriga Nacional’, building on previous evidence that CF alters the vine physiology. A targeted UPLC-MS analysis was used to identify treatment effects on 54 metabolites, including phenolic acids, stilbenoids, flavonols, and flavan-3-ols. PCA and OPLS-DA showed that woody canes from CF vines have distinct metabolic profiles, with stilbenoids increasing consistently. Notably, there was an increase of E-resveratrol (7-fold), E-piceatannol (7-fold), and E-ε-viniferin (7-fold), compounds that are recognised to play crucial roles in boosting the plant’s defence mechanisms. On the other hand, flavan-3-ols like procyanidin B1 showed a consistent decrease in both vintages by up to 24 %. These findings suggest that CF promotes the accumulation of stilbenes and the reduction of flavonols and flavan-3-ols in grapevine canes.